Faktor Penyebab Contract Change Order pada Proyek Konstruksi Sumber Daya Air Padang Pariaman - Jonadi, Jonadi; Mizwar, Zuherna; Utama, Wahyudi P (Universitas Batanghari Jambi, 2024)
Government infrastructure projects in water resources projects generally apply a unit price contract system. This is because implementing a unit price contract system is not difficult and is balanced in terms of sharing risks from contract changes between providers and users of construction services. In the unit price contract system, it is very possible for contract changes to occur on construction projects. Changes in the implementation of construction projects can occur repeatedly and are difficult to avoid. The aim of the research is to identify the factors that cause Contract Change Orders and the dominant factors that cause them during the implementation phase of construction projects in the water resources sector. The research was carried out by distributing questionnaires to respondents involved in water resources construction project work at the Padang Pariaman PUPR Service for the 2019 to 2021 budget year and then carrying out factor analysis. In research on the factors that cause Contract Change Orders to occur during the implementation phase of water resources construction projects in Padang Pariaman Regency, there are 4 factors that cause Contract Change Orders during the implementation phase of water resources construction projects, namely managerial factors, regulatory factors. from parties who have the authority to make decisions, planning factors, design change factors. The dominant factor that causes the Contract Change Order to occur during the implementation stage of a water resources construction project is the managerial factor.